Comparative Proteomics in Caries Active and Caries Free Associated S. Mutans Strains for Metabolic Remodeling Favouring Colonization - Samer Salim Abed, P. Kiranmayi, Venkata Kolli, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: A multifactorial condition, dental caries is primarily brought on by cariogenic bacteria that are frequently present in the mouth. Caries infections are commonly associated with the acid-producing bacteria Streptococcus mutans. If left untreated, dental caries can result in tooth decalcification, cavities, hypersensitivity, and even tooth loss. Comparative proteomics by Mass spectrometry was carried out to reveal caries-associated metabolic remodeling in S mutans isolates favouring biofilm formation and colonization. Methods: We conducted a differential proteomic analysis to determine the differences in protein expression between S.mutans strains linked to dental caries and those present in a healthy oral microbiome. High-performance mass spectrometry (MS) using Orbitrap, has led to the development of proteomics in larger-scale protein analysis. Five clinical specimens from individuals who had caries disease (Caries active) were compared with two isolates from the healthy oral dental microbiota (Caries free). Protein samples were digested, and a peptide mixture investigation was done. Results and Discussion: 3276 proteins that were expressed at comparable amounts in both groups of bacteria and were found by proteomic analysis. Only 39 of these proteins were unique and distinct to group 1 (those without caries), whereas 444 proteins were specific to group 2. (S.mutans from caries patients). Significant differences in the grouping of the control (Caries free) and caries (Caries active) samples were seen through PCA analysis. 23 Significantly regulated proteins in S. mutans bacteria were discovered (p < 0.05, t-test). Among these, 23 differentially expressed proteins, 10 were upregulated, and 13 downregulated. By Identifying differential peptides and proteins, their quantification, and appropriate bioinformatic analysis, there are insights into formation of biofilm by S. mutans in dental caries and potential targets for intervention using various antagonists/ nanoparticle approaches as alternatives to conventional antibiotics.